Children of the Americas: child survival, protection and integrated development in the 1990s (UNICEF BogotaCO, 1992)
Focuses on children in Latin America and the Caribbean. Looks at children in relation to sustainable development, poverty, health, nutrition, education and water and sanitation. Examines the convention on the Rights of the Child and national programmes and looks at courses of action. Sets goals for the 1990s.
DC